Ethical and Legal Issues in the Use of Online-Based Health Services (E-Health) - Fitriani Nur Damayanti; Absori Absori; Kelik Wardiono; Sri Rejeki (SOEPRA, 2020)
Abstract: The internet offers unprecedented power to provide users with health information for patients, health professionals, and professionals. Maintaining the integrity, data systems, and confidentiality of individual health information, quality of content, and consumer protection and the commercial interests of the health industry against unethical practices, are areas of greatest concern in the implementation and use of the Internet. However, there is no national and international legislation for regulating the use of online-based health services. This research is a Literature review that aims to explore ethical and legal issues in the use of online-based health services (E-Health). The review process begins by identifying journal articles that are relevant to the research topic. This study concludes that the use of online-based health services (E-Health) is an important public health issue. E-Health emerged as a tool for developing new diagnostics and therapeutic interventions. Ethical issues related to crossing clinical practice and online communication about health services. This allows discriminatory or unethical behavior and is not following the professional code of ethics. E-Health licensing standards and regulations have not been implemented in many countries. So that health workers are required to code of ethics in the use of online-based health services (E-Health).